2021
DOI: 10.1007/s11042-021-11004-w
|View full text |Cite
|
Sign up to set email alerts
|

A study on the sentiments and psychology of twitter users during COVID-19 lockdown period

Abstract: The outbreak of the novel Coronavirus in late 2019 brought severe devastation to the world. The pandemic spread across the globe, infecting more than ten million people and disrupting several businesses. Although social distancing and the use of protective masks were suggested all over the world, the cases seem to rise, which led to worldwide lockdown in different phases. The rampant escalation in the number of cases, the global effects, and the lockdown may have a severe effect on the psychology of people. Th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
5
3
2

Relationship

0
10

Authors

Journals

citations
Cited by 42 publications
(11 citation statements)
references
References 47 publications
(25 reference statements)
0
10
0
Order By: Relevance
“…Despite this general definition, however, most research and algorithms developed in the field of natural language processing focus on polarity detection, which aims to represent the emotional content of linguistic entities as scores on a scale from strongly negative to strongly positive (40)(41)(42)(43)(44)(45)(46)(47)(48)(49)(50). Now a fundamental tool of computational text analysis, polarity detection (henceforth polarity) has notably been used in psychology for analyzing sentiment in dreams (51), detecting mental disorders in Tweets (52), diagnosing anorexia nervosa (53,54), and assessing the wellbeing of Tweeters during the pandemic (55).…”
Section: Sentiment Analysismentioning
confidence: 99%
“…Despite this general definition, however, most research and algorithms developed in the field of natural language processing focus on polarity detection, which aims to represent the emotional content of linguistic entities as scores on a scale from strongly negative to strongly positive (40)(41)(42)(43)(44)(45)(46)(47)(48)(49)(50). Now a fundamental tool of computational text analysis, polarity detection (henceforth polarity) has notably been used in psychology for analyzing sentiment in dreams (51), detecting mental disorders in Tweets (52), diagnosing anorexia nervosa (53,54), and assessing the wellbeing of Tweeters during the pandemic (55).…”
Section: Sentiment Analysismentioning
confidence: 99%
“…Additionally, persons who rely on multimedia devices to pass the time during a lockdown may experience severe psychological repercussions such as loneliness and sadness. As a result, there is a need to examine the psychology of the human mind in such a situation [49] .The public sentiment gleaned from numerous reflexions (hashtags, comments, tweets, and Twitter postings) is accurately measured, ensuring that various policy decisions and communications are taken into account [50] . The application exhibits premonition in the improvement of terror sentiment finally as panemicreaches its peak globally by utilising extensive textual analysis with the assistance of essential text data visualisation [51] .Text mining is defined as "the process of extracting useful information from unstructured textual data by identifying and exploring interesting patterns."…”
Section: Related Workmentioning
confidence: 99%
“…Physiological studies have shown that post-traumatic stress (PTSD) affects immune suppression, increases susceptibility to disease and leads to an indelible vicious cycle [20], yet effective social activities can mitigate the effects of PTSD. An affective computing study comparing Twitter users' tweets during the epidemic found that they were more inclined to post positive and upbeat tweets than before, suggesting that the socializability of good digital products can actually improve users' mental health [30]. Thus, intelligent recommendation systems will play an important role in helping users to target potential social objects, people and content during the socialisation process.…”
Section: Apply Ai To Enhance the Playfulness Of Somatic Gamesmentioning
confidence: 99%